An Experimental Study on the Effect of Water–Cement Ratio on Non-Shrink Grout Performance under Extreme Temperature Conditions - Mohamad Asep Triono; Suheryanto (Universitas Medan Area, 2026)
This study investigates the influence of the water–cement ratio (W/C) on the performance of non-shrink grout mixed with cold water under extreme temperature conditions. High ambient temperatures accelerate cement hydration, shorten the working time, and may reduce the mechanical performance of grout. Therefore, this research aims to determine the optimum W/C ratio capable of improving grout quality while maintaining adequate workability under hot environmental conditions. An experimental laboratory method was employed using SikaGrout-215 with five W/C ratios of 0.50, 0.33, 0.25, 0.20, and 0.16. The specimens were tested for bulk density, compressive strength at 7, 14, and 28 days, and initial setting time using the Vicat apparatus. The results indicate that reducing the W/C ratio significantly increased the bulk density and compressive strength while shortening the initial setting time. The optimum performance was achieved at a W/C ratio of 0.16, producing the highest 28-day compressive strength of 49.72 MPa and the densest grout structure. These findings demonstrate that combining a low W/C ratio with cold mixing water effectively enhances grout performance under high-temperature conditions and provides practical guidance for grouting applications in tropical environments.